Cultural theory and popular culture : an introduction - Storey, John (Oxon: Routledge, 2021)
In this ninth edition of his award-winning introduction, John Storey presents a clear and critical survey of competing theories of and various approaches to popular culture. Its breadth and theoretical unity, exemplified through popular culture, means that it can be flexibly and relevantly applied across a number of disciplines.
In English.
P.B
Keywords: Culture-Philosophy; Culture-History